Comprimento telomérico e risco de desnutrição/ desnutrição: estudo transversal com pessoas idosas da comunidade - Rodrigues, Priscila Cristina De Oliveira Garcia (2023)
The increasing of life expectancy comes attached with the successful aging. Therefore, biomarkers, such as the telomere length, are essential to have a better comprehension of the aging process. The telomers protect the genetic material and its shortening is associated with the life expectancy’s decrease and the risk of disease’s increase. The objective of this research is to verify if the shortest telomere length is associated with the innutrition risk in older people. Cross-sectional study accomplished with probabilistic sample of 448 old-aged people resident of the municipality of Alfenas-MG. The data collection was carried out in two steps, first with a personal interview and then with a blood collection. The blood sample was used for relative quantitative of telomeres length through qPCR in real time. The malnutrition risk was identified through the Mini Nutritional Evaluation. The distinction between the groups was estimated by using the x2 tests of Pearson and Exato de Fisher. The multiple logistic regression was used for the association analyses. By the evaluated participants, it was observed a greater proportion of women (70.76%), aged between 60 and 69 (45,31%). The innutrition risk was observed in 34,15% of the sample, which showed that older people with shortest telomere length had more chances of getting malnutrition (OR= 1,63; IC95%= 1,04-2,55) compared to those with longer telomeres, independent of age groups, family income, multimorbidity, cognitive decline and depressive symptoms. With the expressive increase of numbers of old-aged people and the damage that the low weight and the malnutrition cause to this population, an early diagnosis enables early interventions to maintain a better life expectancy and health of these individuals. The usage of the telomere length as an aging biomarker, associated with the nutritional status, will contribute to the development of clinical trials, assisting in the implementation of interventions to prevent and treat the risk of innutrition.